Review of "Un día de guerra (Visión estelar)"; "La Media Noche. Visión estelar de un momento de guerra" de Ramón del Valle-Inclán. Estudio y edición de Bénédicte Vauthier y Margarita Santos Zas (2017) (Prassi Ecdotiche della Modernità Letteraria, 2018)
Review of the three-volumes reliable and meticulous edition of La media noche by Ramón del Valle-Inclánis edited by Bénedicte Vauthier and Margarita Santos Zas and published by the Universidade de Santiago de Compostela(Cátedra Valle-Inclán) in cooperation with the Grupo de Investigación Valle-Inclán-USC (2017).